Training Detection of Preeclampsia Risk Factors for Physicians in Primary Care with Experience-Based Learning Methods: A Quasi Experimental Study - Brantas Prayoga; Shinta Prawitasari; Mora Claramita (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
Background: Training for primary care physicians in the management of pregnant women often combines detection of the risk of bleeding, risk of infection and the risk of preeclampsia. Meanwhile, preeclampsia contributes to the world's largest maternal mortality rate, including in Indonesia. Primary care physicians’ knowledge about the risk factors and the early detection of preeclampsia is still very limited. It is therefore necessary to detect preeclampsia risk factors as early as possible and perform proper, fast and effective therapeutic diagnosis to prevent the onset of preeclampsia and to make efforts to safeguard maternal health and the survival and wellness of her baby. Experiential learning was selected in this training as it allows for sustainable learning.Methods: Quasi experimental study was conducted with 30 physicians of Community and Primary Health Care Center (Puskesmas) who were randomly divided into 2 groups, i.e. treatment group and control group each with 15 people. The treatment group was given training by 2 cycles of experiential learning, then both groups rated knowledge with vignette questionnaires from international sources that have been validated by experts in obstetrics, with 1-week interval time between the post-test and pre-test.Results: There was an increase of knowledge in primary care physicians after receiving training for both the treatment group (p = 0.034) or the control group (p = 0.000). The increase of knowledge in the treatment group after training was higher than the control group with the mean difference of 5.733. This result shows that the use of experiential learning methods proved effective.Conclusion: The detection training of risk factors for preeclampsia increases the physician's knowledge in managing preeclampsia in primary care.